Low-Burden Universal Substance Use Screening in a Primary Care Clinic to Lower Implementation Barriers - Konkle-Parker, Deborah; Williams, Daniel; McAfee, Nicholas; Schumacher, Julie A.; Parker, Jefferson (The journal of behavioral health services & research, 2023)
Universal substance use screening in primary care can proactively identify patients for intervention, though implementation is challenging. This project developed a strategy for universal low time- and labor-cost screening, brief intervention, and referral for treatment (SBIRT) in an HIV primary care clinic at an academic medical center in the Southeastern USA. Screening was implemented using a tablet computer that calculated results in real time and suggested motivational language for provider response. A brief intervention (BNI) was conducted by a trained professional as needed, preventing the need for all clinic providers to be competent in motivational interviewing (MI). More than 1868 patients were screened in 12 months, with an MI intervention conducted for 101 patients with higher risk use. Forty-four patients were referred for in-clinic treatment, compared to nine in the previous year. Computer-based, self-administered screening with real-time linkage to a BNI can allow recommended screening with low provider burden.